Acute and sub-chronic toxicity study of standardized extract of Fumaria indica in rodents - Singh G.K.; Kumar V. (My University, 2025)
Ethnopharmacological relevance: Despite Fumaria indica (FI) widespread medicinal uses in the Indian traditional medicine, no systematic study of the potential toxicity of the plant has been described. Aim of the study: To assess acute and sub-chronic toxicity of a 50% ethanolic extract of FI in mice and rats respectively. Materials and methods: In acute toxicity study, Swiss strain albino mice of either sex were administered orally FI doses of 1, 2.5 and 5 g/kg and observed for behavioural changes and mortality, if any. In sub-chronic toxicity study, Charles Foster albino rats of either sex were administered two doses of FI i.e., 100 and 400 mg/kg, p.o. for 30 consecutive days. During 30 days of treatment, rats were observed for any change in body weight and daily food and water intake. After 30 days, rats were sacrificed for haematological, biochemical and histopathology study. Control animals were administered 0.3% carboxymethyl cellulose (CMC) suspension by oral route. Results: There was no mortality or abnormal behaviour, observed in acute toxicity study in mice at all the three dose levels. In sub-chronic toxicity study, FI did not produce any significant change in body weight and daily food and water intake of rats when compared to vehicle treated rats. Further, haematological and biochemical parameters were also found normal. Histopathological study revealed normal architecture of kidney and liver of FI treated rats. Conclusions: FI extract, provisionally standardized on its fumarate contents, seems to fulfill a preclinical criterion necessary for its further development as a clinically useful adaptogen. © 2011 Elsevier Ireland Ltd.